2004
DOI: 10.1007/s10227-003-0110-4
|View full text |Cite
|
Sign up to set email alerts
|

Scar Area and Cosmetic Outcome After Circular and Elliptical Excision of Small Skin Lesions

Abstract: Circular excisions seemed to cause smaller scars and equal cosmetic results compared with traditional elliptical excisions and could therefore be an alternative method for small skin excisions on the trunk and extremities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…A prospective analysis of 41 patients undergoing elliptical and round excisions closed with dog ear repairs found that the overall wound length was 14% shorter for round excisions, most notably in the trunk, scalp, and other areas with thick skin (43). These findings are supported by additional reports of decreased scar length in punch compared to elliptical excisions (44,45).…”
Section: Wounds Outcomes and Scarringmentioning
confidence: 92%
See 1 more Smart Citation
“…A prospective analysis of 41 patients undergoing elliptical and round excisions closed with dog ear repairs found that the overall wound length was 14% shorter for round excisions, most notably in the trunk, scalp, and other areas with thick skin (43). These findings are supported by additional reports of decreased scar length in punch compared to elliptical excisions (44,45).…”
Section: Wounds Outcomes and Scarringmentioning
confidence: 92%
“…Although traditional elliptical excisions allow for primary closure with minimal risk for dog-ear deformity, the overall tissue loss and final scar length are suboptimal (42). Several other techniques, including round, punch, and staged excisions, may decrease the scar length while maintaining a low risk of dog-ear deformity (42)(43)(44)(45).…”
Section: Wounds Outcomes and Scarringmentioning
confidence: 99%
“…2 Another common dermasurgical technique is the round excision with dog ear repairs, that can obtain a similar or even better aesthetic outcome and a lower scar length, according to some researches. 4,5 Regardless the surgical procedure, the excision lines are generally marked preoperatively on the skin using a skin-marking pen, but after the cutting, the cutaneous elasticity, insisting perpendicularly to the Langer's lines,…”
mentioning
confidence: 99%
“…The mean lengths of the wounds in the punch incision and elliptical excision groups were 0.73 and 2.34 cm, respectively 18 . Ek and colleagues also compared circular and elliptical excisions in 56 patients and found that circular excisions formed smaller scars and resulted in an equal cosmetic outcome 19 …”
mentioning
confidence: 99%
“…18 Ek and colleagues also compared circular and elliptical excisions in 56 patients and found that circular excisions formed smaller scars and resulted in an equal cosmetic outcome. 19 Dog ears are not always avoidable, although there are studies that indicate that they self-resolve. A 2008 report followed 43 dog ears after excisions in 26 patients and quantified dog ear regression.…”
mentioning
confidence: 99%